Exploring the Obstacles Faced by Teachers and Their Coping Strategies in Mother Tongue-Based Education - Jr, Leo L. Codilla; Andig, Junnah Mae P.; Aray, Catherine A.; Boncato, Giezza Mae P. (International Journal of Membrane Science and Technology, 2023)
This study aimed to explore the obstacles faced by teachers in Mother Tongue-Based Education (MTB) and their coping strategies. Specifically, it focused on investigating the challenges encountered by teachers in MTB. The study examined the extent of challenges in terms of the availability of instructional materials (IMs), strategies used, and training attended by teachers. Additionally, the level of coping strategies employed by teachers in terms of lesson delivery and IM availability was assessed. The relationship between teachers' challenges and coping strategies in MTB was further explored, and the findings were utilized to develop interventions. Using a descriptive-correlational research design, the study revealed that teachers faced obstacles primarily due to the lack of digital resources and inadequate training, which consequently affected the availability of essential teaching strategies. However, despite these challenges, teachers demonstrated effective coping strategies. They employed various approaches to teach their lessons and achieve their desired objectives, while also utilizing diverse resources to foster a collaborative and interactive learning environment. Moreover, the study found no significant relationship between the extent of teachers' challenges and their level of coping strategies in MTB. Based on the findings, it is recommended that schools provide teachers with targeted training and professional development opportunities specifically related to MTB. By addressing the identified challenges, teachers can enhance their coping strategies and improve the overall effectiveness of MTB education.